2018
DOI: 10.3389/fchem.2018.00020
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Accumulation of Acetaldehyde and Strecker Aldehydes during Red Wine Oxidation

Abstract: The main aim of the present work is to study the accumulation of acetaldehyde and Strecker aldehydes (isobutyraldehyde, 2-methylbutanal, isovaleraldehyde, methional, phenylacetaldehyde) during the oxidation of red wines, and to relate the patterns of accumulation to the wine chemical composition. For that, eight different wines, extensively chemically characterized, were subjected at 25°C to three different controlled O2 exposure conditions: low (10 mg L−1) and medium or high (the stoichiometrically required a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 74 publications
8
58
1
Order By: Relevance
“…In the Shiraz, both SO 2 and Cu treatments increased the concentrations of 3-methylbutanal and phenylacetaldehyde at PAF, which then decreased significantly (p ≤ 0.05) until PB, when no difference amongst treatments was found ( Figure 2D,F). The increase in phenylacetaldehyde concentration during red wine aging, as observed in Figure 2F, has also been reported by Bueno et al [56], who indicated that this compound was less reactive to flavonoids than other Strecker aldehydes.…”
Section: Impact Of Cu or So 2 Addition To Juice/must On Total Concentsupporting
confidence: 87%
See 1 more Smart Citation
“…In the Shiraz, both SO 2 and Cu treatments increased the concentrations of 3-methylbutanal and phenylacetaldehyde at PAF, which then decreased significantly (p ≤ 0.05) until PB, when no difference amongst treatments was found ( Figure 2D,F). The increase in phenylacetaldehyde concentration during red wine aging, as observed in Figure 2F, has also been reported by Bueno et al [56], who indicated that this compound was less reactive to flavonoids than other Strecker aldehydes.…”
Section: Impact Of Cu or So 2 Addition To Juice/must On Total Concentsupporting
confidence: 87%
“…Examples included 2-methylpropanal, 3-methylbutanal, phenylacetaldehyde, hexanal, benzaldehyde, and methional. Bueno et al [56] reported a negative relationship between the accumulation of certain volatile aldehyde compounds in bottle aged red wines with the concentration of aldehyde-reactive phenolic compounds. The latter phenolic compounds included anthocyanins and procyanidins.…”
Section: Impact Of Cu or So 2 Addition To Juice/must On Total Concentmentioning
confidence: 99%
“…For this, it has a pivotal role, while nonetheless being a marker to be controlled to avoid wine oxidative spoilage. In particular, it reacts very rapidly with SO −3 to produce an insoluble, less aromatic disulfite adduct [ 100 ]. For this reason, if SO 2 is not added to the wine, acetaldehyde will probably be the predominant aroma [ 30 ].…”
Section: Desired Chemical Changesmentioning
confidence: 99%
“…They found that the type of aldehydes was a function of the SO 2 concentration, with the production of some aldehydes being very SO 2 dependent (saturated aldehydes C 1 -C 9 ), others less so (formaldehyde, propanal, pentanal, hexanal, heptanal) and some not at all (butanol) [4]. Other researchers identified that the type of aldehydes produced was dependent on the amino acids present [5].…”
Section: Introductionmentioning
confidence: 99%